2001
DOI: 10.1074/jbc.m009037200
|View full text |Cite
|
Sign up to set email alerts
|

The DNMT1 Target Recognition Domain Resides in the N Terminus

Abstract: DNA-cytosine-5-methyltransferase 1 (DNMT1) is the enzyme believed to be responsible for maintaining the epigenetic information encoded by DNA methylation patterns. The target recognition domain of DNMT1, the domain responsible for recognizing hemimethylated CGs, is unknown. However, based on homology with bacterial cytosine DNA methyltransferases it has been postulated that the entire catalytic domain, including the target recognition domain, is localized to 500 amino acids at the C terminus of the protein. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 43 publications
3
36
1
Order By: Relevance
“…Nearly identical behavior of the truncated enzyme with all the substrates, including preferred methylation of hemimethylated DNA, clearly indicates that the N-terminal region containing the binding sequences for DNA and PCNA is dispensable for the selectivity of Dnmt1 toward hemimethylated sites. Araujo et al (25) reported that the targeting sequence for hemimethylated DNA resides in the N-terminal domain near the PCNA recognition site; however, our present results show that the N-terminal domain containing the PCNA site is dispensable for the preferential methylation of Dnmt1 toward hemimethylated DNA.…”
Section: Enzymatic Activities Of Recombinant Dnmt1-fl and Dnmt1-dn-contrasting
confidence: 56%
See 2 more Smart Citations
“…Nearly identical behavior of the truncated enzyme with all the substrates, including preferred methylation of hemimethylated DNA, clearly indicates that the N-terminal region containing the binding sequences for DNA and PCNA is dispensable for the selectivity of Dnmt1 toward hemimethylated sites. Araujo et al (25) reported that the targeting sequence for hemimethylated DNA resides in the N-terminal domain near the PCNA recognition site; however, our present results show that the N-terminal domain containing the PCNA site is dispensable for the preferential methylation of Dnmt1 toward hemimethylated DNA.…”
Section: Enzymatic Activities Of Recombinant Dnmt1-fl and Dnmt1-dn-contrasting
confidence: 56%
“…The PCNA complex with replication machinery slides on DNA (29,30), and the interaction of Dnmt1 with PCNA facilitates activity toward hemimethylated DNA (13). As well, the hemimethylated DNA targeting sequence in Dnmt1 was reported to reside near the PCNA binding site (25). Interactions of the N-terminal domain of Dnmt1 with DNA and PCNA may contribute to ensuring the immediate early methylation of the hemimethylated form of newly synthesized DNA strands to maintain methylation patterns at the replication fork.…”
Section: The N-terminal Domain Is Dispensable For Both the Preferentimentioning
confidence: 99%
See 1 more Smart Citation
“…A number of biochemical studies suggested that conformational change and the interaction between the N-terminal region and the C-terminal catalytic domain play important roles in DNMT1 function (1,2,17,25,38). Our results suggested that, unlike full-length DNMT1, the N-terminal domain of DNMT1 associated with unmethylated chromatin, and the RFT/TS domain was responsible for this function (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…DNMT1 localizes to the replication fork 42 where it associates with PCNA (the replication processivity protein), 43 and association with the hemimethylated sequence has been localized to the N-terminal domain. 44 DNMTs 3a and 3b are classified as de novo methyltransferases; they bind to both hemimethylated and unmethylated CpG sites and add methyl groups to previously unmethylated cytosines. De novo methylation occurs extensively during early development and, once the methylation patterns are established, appear to be faithfully maintained for the life of the dividing cell.…”
Section: Metabolic Pathways and Mechanisms Of Regulationmentioning
confidence: 99%